2021
DOI: 10.1002/aelm.202001216
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Engineering of Hf‐Doped InZnSnO Films for High‐Performance and Stability Amorphous Oxide Semiconductor Thin Film Transistors

Abstract: be employed as transparent TFTs. [13][14][15] Recently, rapid advance in transparent electronic devices for transparent TV, mobile, wearable, and even VR devices require the development of transparent TFTs and their high-performance channel layers. Moreover, AOS-based TFTs could meet the requirement of the next-generation organic light emitting diode TV, such as ultra-high frame rate, larger size, and higher resolution, due to their high mobility. [16,17] Among various metal oxide semiconductor channel materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…As a result, composition is often used as a default experimental variable because of its easiness to be clearly qualitatively and quantitatively expressed contrary to the other above-mentioned basic matter properties. Moreover, the thin film composition can be directly influenced by the applied deposition conditions in case of multisource depositions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, composition is often used as a default experimental variable because of its easiness to be clearly qualitatively and quantitatively expressed contrary to the other above-mentioned basic matter properties. Moreover, the thin film composition can be directly influenced by the applied deposition conditions in case of multisource depositions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…When considering physical vapor deposition, basically three approaches towards composition-dependent property studies exist. The first approach consists in single-source depositions of the required materials [ 5 , 10 , 11 ]. This approach, however, requires a set of source materials to cover the entire selected thin film compositional range and, therefore, it is extremely source demanding in term of the materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contradiction to ITO that crystallizes rapidly at very low temperatures (<150 °C), Zn atoms have been proven to stabilize the amorphous phase of InZnO (IZO) to a high temperature of 500 °C. , Amorphous IZO thin films with a uniform and isotropic microstructure are less prone to fracture and more pliable owing to the lack of grain boundaries . Moreover, previous reports have demonstrated that the incorporation of third cations having a higher ionic valence and stronger metal-oxide bond dissociation energy than In 3+ can suppress oxygen vacancy (V O ) formation in In 2 O 3 and thus reduce the carrier concentration, which in turn tailors the optical and electrical properties of the IZO thin film as both the transmittance and resistivity are related to the carrier concentration in the thin film. , Although a number of dopants such as B, Ga, Gd, Hf, La, Sc, Si, Sr, Ta, Ti, W, Y, Zr, etc. have been incorporated into IZO as the carrier suppresser, there are still many other candidates that have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%